Religious Expression of Hijrah Celebrity: Accommodating Protest and Political Economy of Public Piety - Afrida Arinal Muna (Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi, 2020)
The hijrah campaign or massive movement that invites Muslims to become a better person by practicing religious teachings is more vigorously voiced in the digital era, including on social media, as we can find on ‘detiknews’ that the hastag #hijrah in the instagram search box more than 1,7 million posts. The hijrah account on facebook has also been followed by more than 300 thousand accounts. This phenomenon cannot be denied also by the artists, because this phenomenon is massive in the middle to upper class, who have the opportunity to consume issues trending or viral on social media. The trend in hijrah activities also influenced a series of celebrities who decided to hijrah with different processes. I assume that celebrities who do hijrah actually want not only to show their new religious expression by showing their peity to the public but also to be a form of ‘accomodating protest’ that before they decide to hijrah, there is a kind of bullying that is the emergence of stigmas of a fear of a decline in their image in public when an artist hijrah with his new hijab style, but instead there is a kind of resistance that celebrities want to come out to public that they can still exist in even though wearing the hijab. There is also an political economic strategy played by the artists by making some innovations such as halal industry. This is their target because the trends have been becoming a massive consumerism trend by the millenial Muslim middle class, which is believed to be economic booster of the 21st century. Kampanye hijrah atau gerakan massif yang mengajak kaum Muslim untuk menjadi pribadi yang lebih baik dengan menjalankan ajaran agama semakin gencar disuarakan di era digital. di era digital, termasuk di media sosial, sebagaimana dapat kita temukan di ‘detiknews’ bahwa tagar #hijrah di kotak pencarian instagram terdapat lebih dari 1,7 juta postingan, akun hijrah di facebook juga sudah diikuti lebih dari 300 ribu akun. Fenomena ini tidak bisa dinafikan juga dari kalangan artis, karena fenomena ini masif ditemui di kalangan kelas menengah ke atas yang berkesempatan mengonsumi isu-isu yang menjadi tren atau viral di media sosial. Tren aktivitas hijrah ini pun mempengaruhi sederet selebriti yang memutuskan untuk hijrah dengan proses yang berbeda-beda. Saya berasumsi bahwa selebriti yang melakukan hijrah sebenarnya tidak hanya ingin menunjukkan ekspresi keberagamaan barunya dengan menunjukkan kesalehannya terhadap publik, tetapi juga sebagai sebuah bentuk ‘accomodating protest‘ bahwa sebelum mereka memutuskan untuk hijrah ada sejenis bully-an yaitu munculnya stigma-stigma ketakutan menurunnya citra mereka di hadapan publik ketika seorang artis melakukan hijrah dengan style hijab barunya, tetapi justru ada semacam perlawanan yang ingin ditunjukkan oleh para selebriti kepada masyarakat bahwa mereka tetap bisa eksis walaupun memakai jilbab dan juga ada strategi politik ekonomi yang dimainkan oleh artis-artis hijrah tersebut dengan membuat inovasi-inovasi industri halal, tren hijab yang semakin down-to-earth, dan yang lainnya. Industri halal tersebut menjadi sasaran mereka karena tren tersebut menjadi tren konsumerisme yang masif oleh kelas menengah Muslim milenial yang diyakini sebagai penggerak ekonomi abad-21.